Pyridostigmine as a therapeutic option for pediatric gastrointestinal dysmotilities in ATR-X syndrome. Case report and literature review - Comisi, F. F.; Soddu, C.; Corpino, M.; Marica, M.; Cacace, R.; Foiadelli, T.; Savasta, S. (Frontiers in Pediatrics, 2024)
BackgroundAlpha-thalassemia X-linked intellectual disability (ATR-X) syndrome, is a rare genetic disorder, caused by mutations in the ATRX gene. Clinical manifestations include typical facial dysmorphisms, mild-to-severe intellectual disability, hypotonia, genital anomalies, significant gastrointestinal (GI) complications, such as abdominal distension, chronic constipation, feeding difficulties, gastroesophageal reflux, and mild-to-moderate anemia secondary to alpha-thalassemia.Case presentationWe report a patient with ATR-X syndrome suffering from gastrointestinal dysmotility and highlight the beneficial effects of pyridostigmine. Knowledge about the role and appropriate dosage of pyridostigmine in GI motility disorders is limited. To date, only nine pediatric cases involving pyridostigmine for GI dysmotility have been reported.ConclusionsConsidering current understanding about the treatment of gastrointestinal complications in patients with genetic syndromes, this case provides new insights into management of these complex clinical presentations.